Regarding the bees : a lesson, in letters, on honey, dating, and other sticky subjects - Klise, Kate (Regarding the ---, 2007)
The seventh graders at Geyser Creek Middle School are preparing for a spelling bee and a horrible standardized test called the BEE, and try to smuggle their mascot--a bee that spells--into the local spelling competition.